Beragama yang Humanis: Sebuah Konstruksi Spiritualitas Persaudaraan Antarumat Beragama melalui Refleksi Teologis Surat-surat Paulus - Gea, Sefen Krisman; Daeli, Gordenisobek (Sekolah Tinggi Teologi Baptis, Jakarta, 2024)
Pluralistic societies need inter-religious brotherhood to strengthen harmony and peace, especially in Indonesia. This study aims to explore the Apostle Paul's humanistic values through textual analysis of Paul's letters and how these values can be applied in building interfaith brotherhood. The methodology used is qualitative analysis with a narrative approach, focusing on Paul's letters such as Romans, 1 and 2 Corinthians, Philippians, Galatians, and 2 Timothy. The study explores the main themes in Paul's texts, which include love, humility, and service as the basis for brotherly relationships. The findings show that Paul's teachings offer concrete guidelines for building harmonious and mutually supportive relationships between religious communities. By understanding and applying the humanistic values of Paul's teachings, individuals can strengthen interfaith relationships and create a more harmonious environment. This research contributes to a more specific understanding of the practice of brotherhood in the context of interfaith interactions. AbstrakMasyarakat majemuk memerlukan persaudaraan antarumat beragama untuk memperkuat kerukunan dan perdamaian, terutama di Indonesia. Penelitian ini bertujuan untuk mengeksplorasi keteladanan humanis Rasul Paulus melalui analisis teks surat-surat Paulus dan bagaimana nilai-nilai ini dapat diterapkan dalam membangun persaudaraan antarumat beragama. Metodologi yang digunakan adalah analisis kualitatif dengan pendekatan naratif, fokus pada surat-surat Paulus seperti Surat Roma, Surat 1 dan 2 Korintus, Filipi, Galatia dan 2 Timotius. Penelitian ini menggali tema-tema utama dalam teks Paulus yang mencakup kasih, kerendahan hati, dan pelayanan sebagai landasan untuk hubungan persaudaraan. Temuan menunjukkan bahwa ajaran Paulus menawarkan panduan konkret untuk membangun hubungan yang harmonis dan saling mendukung di antarumat beragama. Dengan memahami dan menerapkan nilai-nilai humanis dari ajaran Paulus, individu dapat mempererat hubungan antarumat beragama dan menciptakan lingkungan yang lebih harmonis. Penelitian ini memberikan kontribusi pada pemahaman praktik persaudaraan yang lebih spesifik dalam konteks interaksi antarumat beragama.